The Significance of the message of the Resurrection for faith in Jesus - Marxsen, Willi, 1919-; Moule, Charles Francis Digby (London : S.C.M. Press, 1968)
Translation of Die Bedeutung der Auferstehungsbotschaft fur den Glauben an Jesus Christus
Includes papers read to the Theological Commission of the Evangelical Union Church, with an previously published article by W. Marxsen. Includes bibliographical footnotes.
Keywords: Jesus Christ -- Resurrection